Impact of biogenic very short-lived bromine on the Antarctic ozone hole during the 21st century ... : تأثير البروم الحيوي قصير العمر على ثقب الأوزون في أنتاركتيكا خلال القرن الحادي والعشرين ... - Rafael P. Fernández; Douglas E. Kinnison; Jean‐François Lamarque; Simone Tilmes; Alfonso Saiz‐Lopez (OpenAlex, 2017)
Abstract. Active bromine released from the photochemical decomposition of biogenic very short-lived bromocarbons (VSLBr) enhances stratospheric ozone depletion. Based on a dual set of 1960–2100 coupled chemistry–climate simulations (i.e. with and without VSLBr), we show that the maximum Antarctic ozone hole depletion increases by up to 14 % when natural VSLBr are considered, which is in better agreement with ozone observations. The impact of the additional 5 pptv VSLBr on Antarctic ozone is most evident in the periphery of the ozone hole, producing an expansion of the ozone hole area of ∼ 5 million km2, which is equivalent in magnitude to the recently estimated Antarctic ozone healing due to the implementation of the Montreal Protocol. We find that the inclusion of VSLBr in CAM-Chem (Community Atmosphere Model with Chemistry, version 4.0) does not introduce a significant delay of the modelled ozone return date to 1980 October levels, but instead affects the depth and duration of the simulated ozone hole. Our ... : الخلاصة: يعزز البروم النشط المنطلق من التحلل الكيميائي الضوئي لمركبات البروموكربون الحيوية قصيرة العمر (VSLBr) استنفاد الأوزون في الستراتوسفير. استنادًا إلى مجموعة مزدوجة من عمليات محاكاة الكيمياء والمناخ المقترنة بين 1960 و 2100 (أي مع وبدون VSLBr)، نظهر أن الحد الأقصى لاستنفاد ثقب الأوزون في أنتاركتيكا يزداد بنسبة تصل إلى 14 ٪ عند النظر في VSLBr الطبيعي، وهو ما يتوافق بشكل أفضل مع ملاحظات الأوزون. يتجلى تأثير 5 pptv VSLBr الإضافي على الأوزون في أنتاركتيكا بشكل أكثر وضوحًا في محيط ثقب الأوزون، مما ينتج عنه توسع في مساحة ثقب الأوزون تبلغ 5 ملايين كيلومتر مربع، وهو ما يعادل حجم الشفاء من الأوزون في أنتاركتيكا الذي تم تقديره مؤخرًا بسبب تنفيذ بروتوكول مونتريال. نجد أن إدراج VSLBr في CAM - Chem (نموذج الغلاف الجوي المجتمعي مع الكيمياء، الإصدار 4.0) لا يؤدي إلى تأخير كبير في تاريخ عودة الأوزون النموذجي إلى مستويات أكتوبر 1980، ولكنه يؤثر بدلاً من ذلك على عمق ومدة ثقب الأوزون المحاكي. يُظهر تحليلنا كذلك أن إجمالي تدمير الأوزون الناتج عن البروم في طبقة الستراتوسفير السفلى يتجاوز تدمير الكلور بحلول عام 2070 ويشير ...